Integrated lncRNA function upon genomic and epigenomic regulation - Herman, Allison B; Tsitsipatis, Dimitrios; Gorospe, Myriam (Molecular cell, 2022)
Although some long noncoding (lnc)RNAs are known since the 1950s, the past 25 years have uncovered myriad lncRNAs with diverse sequences, structures, and functions. The advent of high-throughput and sensitive technologies has further uncovered the vast heterogeneity of lncRNA-interacting molecules and patterns of expressed lncRNAs. We propose a unifying functional theme for the expansive family of lncRNAs. At an elementary level, the genomic program of gene expression is elicited via canonical transcription and post-transcriptional mRNA assembly, turnover, and translation. Building upon this regulation, an epigenomic program refines the basic genomic control by modifying chromatin architecture as well as DNA and RNA chemistry. Superimposed over the genomic and epigenomic programs, lncRNAs create an additional regulatory dimension: by interacting with the proteins and nucleic acids that regulate gene expression in the nucleus and cytoplasm, lncRNAs help establish robust, nimble, and specific transcriptional and post-transcriptional control. We describe our present understanding of lncRNA-coordinated control of protein programs and cell fate and discuss challenges and opportunities as we embark on the next 25 years of lncRNA discovery.